Method to optimize the learning of mathematics in high school students, through programming logic - Vivanco Aldón, Luis Francisco (2022)
The science courses are and will be the basis of the students' knowledge, in this sense the mathematics course is considered the most important course because in its content it presents topics related to calculus, making their learning of vital importance in the design of educational processes. Finance a review of the state of the art we find a series of works dedicated to being able to enhance the mechanisms used for teaching, from the use of scientific calculators to reaching certain computer programs of common use, in this work a methodology is developed to be able to enhance the programming skills that teachers have in a specific area of programming, where we can consider any programming language but also any computer tool such as Excel spreadsheets. The methodology proposes the organization of topics as specific theories, such as algebra, arithmetic, trigonometry, geometry, where specific functions are developed for each specific topic, with the intention that they can be understood more easily and in turn not complicated. to the teacher in his process of adaptation of the materials and in the development of the classes. The intention is to enhance the knowledge that teachers have instead of presenting a new programming language and that they can learn in order to teach. The results show that by using the knowledge they have regarding some computer tool, we managed to organize the study materials so that it is more understandable at the time of the classes. As a conclusion we can indicate that in these times of the COVID-19 product pandemic, the methodology that is presented becomes more important because the classes are online and can help the learning of mathematics with the help of these mechanisms to organize the study materials and improve the learning processes of the math course.